Gestão de riscos em cadeias de suprimentos: estudo exploratório sobre a experiência brasileira - Marina Guimaraes Mattos (2011)
Aligned to the latest researches concerning risk analysis, this dissertation proposes a study of Brazilian attitudes and behaviors towards supply chains management. While supply chains andglobalized operations generate increases on average transportation distance and supply partners reliance, companies seek for resiliency while reducing inventory and managing regional conflicts. This work contains a literature review on risk management and conducts a field survey that targets Brazilian companies. A survey on risk management of Brazilian supply chains was applied according to international technical and ethical procedures to discover factors that contribute to increase vulnerability on supply chains and Brazilian companies risk management involvement degree